Biocatalysis of ursolic acid by the fungus Gliocladium roseum CGMCC 3.3657 and resulting anti-HCV activity. Issue 29 (3rd May 2018) - Fu, Shaobin; Meng, Qingfeng; Yang, Junshan; Tu, Jiajia; Sun, Di-An
Abstract : Biocatalysis of ursolic acid (UA1 ) by Gliocladium roseum CGMCC 3.3657 was investigated. Abstract : Biocatalysis of ursolic acid (UA1 ) by Gliocladium roseum CGMCC 3.3657 was investigated. Baeyer–Villiger oxidation was found to occur during the reaction. Four metabolites were isolated from the cultures and their structures were identified as 21-oxo, A-homo-3 a -oxa-urs-12-en-3-one-28-oic acid (2 ), 21-oxo-3, 4-seco-ursan-4(23), 12-dien-3, 28-dioic acid (3 ), 21β-hydroxyl-A-homo-3 a -oxa-urs-12-en-3-one-28-oic acid (4 ) and 21β-hydroxyl-3, 4-seco-ursan-4(23), 12-dien-3, 28-dioic acid (5 ), based on their NMR and MS spectral data. All of the four metabolites were new and their anti-HCV activity was tested. Their biotransformation pathway was also proposed.